Carbohydrate Fermentation Patterns of Neisseria meningitidis Determined by a Microtiter Method - Davies, J. A. (1971)
A carbohydrate fermentation technique has been developed and compared to the standard fermentation test with cystine-Trypticase-semisolid agar for the identification of Neisseria meningitidis. This new method utilizes Mueller-Hinton broth as a basal substrate and is performed with microtiter methods. By using Mueller-Hinton broth with and without the addition of antibiotics, the method can be adjusted to test the fermentation patterns of all of the Neisseria including N. gonorrhoeae.